2018
DOI: 10.1007/s13318-018-0478-6
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the CYP3A5*1 Allele on the Pharmacokinetics of Tacrolimus in Japanese Heart Transplant Patients

Abstract: Similar concentration-time curves for tacrolimus were obtained in the expresser and non-expresser groups by dose adjustment based on therapeutic drug monitoring. These results demonstrate the importance of the CYP3A5 genotype in tacrolimus dose optimization based on therapeutic drug monitoring after heart transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 31 publications
2
6
0
Order By: Relevance
“…Tacrolimus target concentrations are frequently reached in renal recipients within 3 days, which is different from our cohort of heart and lung recipients [31]. Despite the large differences in absorption variability, the observed clearance as well as the variability in clearance was in accordance with earlier reports [14,16,28,30,32]. The distribution volumes in our cohort were only slightly higher than those in another study conducted 1 week after lung transplantation, and both studies had similar distribution volume IOVs [14].…”
Section: Utn14supporting
confidence: 71%
See 1 more Smart Citation
“…Tacrolimus target concentrations are frequently reached in renal recipients within 3 days, which is different from our cohort of heart and lung recipients [31]. Despite the large differences in absorption variability, the observed clearance as well as the variability in clearance was in accordance with earlier reports [14,16,28,30,32]. The distribution volumes in our cohort were only slightly higher than those in another study conducted 1 week after lung transplantation, and both studies had similar distribution volume IOVs [14].…”
Section: Utn14supporting
confidence: 71%
“…However, only a few studies on the pharmacokinetics of oral tacrolimus early after thoracic organ transplantation have been performed. Those studies showed that the pharmacokinetics varied with the patient group considered; for instance, a 40% lower bioavailability was observed in cystic fibrosis (CF) patients, and a 40% higher clearance in cytochrome P450 3A5 (CYP3A5) expressers [11][12][13][14][15][16][17]. Also, a low clearance rate has been observed in heart transplant recipients early post-transplantation [18].…”
Section: Introductionmentioning
confidence: 99%
“…A substantial increase (approximately 2.4-fold) of the initial dose was necessary for the CYP3A5 expressers with CYP3A5*1 allele, whereas minor modification was required for low and normal CYP3A4 expressers carrying CYP3A5*3/*3 (20% decrease and 40% increase, respectively). Our results regarding CYP3A5 genotype dependent dose-requirement were in line with the findings in heart transplant recipients in other studies that a substantial increase in tacrolimus daily dose was necessary for the patients carrying CYP3A5*1 allele 57 , 58 , 60 , 61 . In pediatric heart transplant recipients 58 , the dose-requirement of CYP3A5 expressers was similar to that in the adult recipients in the present study (0.278 and 0.240 mg/kg bodyweight, respectively) 58 .…”
Section: Discussionsupporting
confidence: 92%
“…Meanwhile, CYP3A5, as well as CYP3A4, is involved in TAC metabolism [34], and single nucleotide polymorphism in the CYP3A5 gene, CYP3A5*3 (6986A>G), is associated with alteration in its metabolic activity, thereby affecting the blood concentration of TAC [35]. The CYP3A5 genotype is a factor to be considered for TAC dose adjustment.…”
Section: Rep Induces the Expression Of Various Cyp Subfamilies Wherea...mentioning
confidence: 99%